Створення мультимедійного навчального курсу з української літератури - Голуб, О. А. (ХНУРЕ, 2023)
The work deals with the task of developing an e-learning course on the subject of Ukrainian literature. The course should contain interesting and interactive content that will appeal to pupils and students studying this subject. The course should contain various multimedia components, photos, videos, audio, and interactive games. To create the project, we are considering various analogues of e-courses that have an interesting idea and implementation to improve students' perception of the subject.
Keywords: українська література; навчання